A Potential Development of Breathing Gas Sensor Using An Open Path Fibre Technique - Hadi, Manap; Suzalina, Kamaruddin; M. S., Najib (Elsevier Ltd, 2016)
This paper describes a potential development of Methyl Mercaptan or bad breathing gas measurement in the 200 nm - 250 nm region. Methyl Mercaptan shows a potential peak selection at 204 nm and the absorption cross section spectrum display a similar pattern with the theory. A cross sensitivity analysis is also reported and it shows that there is no discernible interference effects between the Methyl Mercaptan gas with other breathing gases such as carbon dioxide, oxygen and water vapor at 204 nm.